AUDIT OF ATTENDANCE INFORMATION SYSTEM AT MOTORCYCLE FACTORY USING COBIT 5 - Francka Sakti Lee; Johanes Fernandes Andry; Kevin Christianto; Honni Honni; Monica Clara (Jurnal Teknoinfo, 2023)
The change in the fingerprint attendance system into an attendance application is called "Mobile Attendance" according to research at motorcycle factory. The reason is work activities that are usually carried out in the office have now changed to being at home due to the COVID-19 pandemic. Employees are required to carry out the attendance process at certain times by taking photos of themselves or the environment in which they are located. Audit attendance applications in companies using COBIT 5, namely the DSS subdomain on DSS02 Manage Service Requests and Incidents and DSS04 Manage Continuity. The audit is carried out through the company's employee interview method, then measures every management process involved in it. The results obtained in the form of the average value achieved by each process is still less than expected and the value of the gap is quite far. Therefore, it is expected to conduct further research related to the management process in the company